Comparative Study on the Effect of Natural and Synthetic Fibers on the Production of Sustainable Concrete - Saavedra-Flores, E (Walter de Gruyter GmbH, 2025)
The increased concern with the use of environmentally friendly products in construction has led to the search for natural fiber replacements to synthetic fibers used in concrete. This research attempts to understand the trends that result from the addition of natural (hemp and luffa sponge) and synthetic fibers to concrete and its mechanical properties at the micro level. Concrete samples were prepared with fiber volume fractions of 0.4%, 0.8%, and 1.2%, and their compressive and flexural strengths were subsequently determined. Scanning electron microscopy (SEM) and energy dispersive spectroscopy were employed for assessing the fiber pattern and characteristics of the cementitious matrix–fiber interface. It was found that all fibers improved the compressive and flexural strengths of concrete in each blend relative to the reference mix. Most importantly, it was observed that the highest compressive strength of 28.15 MPa was obtained with luffa sponge fibers at 1.2% volume fraction accompanied by an enhancement of flexural strength. This was further supported by SEM analysis, which showed the evidence of the natural fibers’ better distribution on the concrete matrix than the synthetic ones, thus improving the structure. The results of this research underscore the versatility of natural fibers, especially luffa sponge, to be used as a construction material with long-term value. This article offers specific recommendations for civil engineers and construction practitioners who wish to improve concrete performance as well as undertake environmentally conscious construction practices. © 2025 the author(s), published by De Gruyter.